Criteria and Conditions for Determining an Act of Robbery Reviewed from a Criminal Law Perspective - MANGGALA, Ni Kadek Erika; BAGIASTRA, I Nyoman (Protection: Journal Of Land And Environmental Law, 2023)
This research aims to determine the legal comparison of criminal acts of theft and mugging or robbery based on the provisions of Indonesian criminal law. It also helps to understand the requirements and influence of interpretation for the legal determination of criminal acts such as robbery from a legal perspective. This type of research is normative legal research, specifically discussing theft and robbery. The data collection method used in this research is a literature study that reviews literature related to the object of this research. The research results show that the comparison between the Crime of theft and not the Crime of robbery lies in using the article regulations. Suppose the Crime of theft is regulated in Article 362 of the Criminal Code. Meanwhile, Article 365 of the Criminal Code regulates the Crime of robbery. Article 365 of the Criminal Code provides a strong legal basis for criminalizing and punishing perpetrators of criminal acts of theft with violence. Correct legal interpretation of Article 365 of the Criminal Code is very important to ensure fair and effective law enforcement against perpetrators of these criminal acts.